Analisis Ekonomi Produk Shampo Rambut Merk Sunsilk - Maulana, Arif Fikri; Zaelani, Ahmad; Hidayat, Syamsul (Populer: Jurnal Penelitian Mahasiswa, 2025)
This study aims to analyze consumer behavior regarding the use of Sunsilk shampoo, including usage experience, duration, reasons for product choice, and customer satisfaction levels. A survey was conducted involving 93 respondents, addressing their experiences and preferences for Sunsilk shampoo. Results revealed that the majority of respondents have used Sunsilk, with product quality and affordable pricing being the primary reasons for their choice. The study also highlights areas for improvement to enhance customer loyalty and satisfaction, offering valuable insights for market strategies.